Progress in Pattern Recognition, Image Analysis and Applications - Ruiz-Shulcloper, José (Springer, 2017)
This book constitutes the refereed proceedings of the 13th Iberoamerican Congress on Pattern Recognition, CIARP 2008, held in Havana, Cuba, in September 2008.